Interviews that work a practical guide for journalists - Biagi, Shirley (Wadsworth Pub. Co., 1992)
Intended as a supplement for any journalism course where interviewing is a substantial skills component. Typically, these include newswriting, report, and broadcast newswriting. There are also separate courses in interviewing and information gathering where the book may serve as a core text.